Identifying The Contract Risks in Selection of Contractor - Shah, Sayed Ghazanfar Ali; Pathan, Ashfaque Ahmed (Tropical Scientific Journal, 2022)
From an economic and social standpoint, construction is an essential and substantial output of any developed or emerging country. It provides the necessary framework for leading a happy and prosperous life. As a result, it is always assumed that all construction projects must be effectively completed in order to reap the benefits of the project. Contractor selection is one of the most critical elements in determining the success of any project. From the previous studies, total 40 contract risks were identified through literature mapping and were prioritized to include through unstructured questionnaire survey from Contract experts to further identification of extremely significant contract risks involved in contract management , These experts opinions were conducted and gathered from highly professional members in Pakistan having Bachelors of Civil participated in higher percentage i.e., 54 and people having Masters in Civil participated in percentage 39 and rest 8 percent were participated by Ph.D. students. Based on probability of the occurrence and level of significance, average index values were calculated. From the results it was observed that out of forty contract risks, seven are in range of extremely significant, twenty-two are in range of significant contract risks. The analyzed results highlighted that risk in selection of contractor and many other parameters affect quality of construction projects.